Kesiapan Perubahan Organisasi Di Dalam Melakukan Transformasi Digital Berdasarkan Model Knoster - Haludin, Guntur; Indrajit, Richardus Eko; Dazki, Erick (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
This article examines readiness for change and conducts a readiness study on the digital transformation of online survey outputs based on various industrial backgrounds in Indonesia using the Knoster model. The study results show that the highest preparation aspect is the company vision, with skills, incentives, resources, and work planning. In that order, significantly reduced in other elements. The large gap between the idea and other features shows that the organization has a strong desire.